Revealing the semantic and spatial evolution of historical landscapes through the mixed-method approach: a case study of Alaca Höyük - Türk, Arzu (Graduate School, 2025)
Landscape is a constantly changing cultural and natural environment. It holds both abstract and concrete meanings, and these meanings are redefined in different geographies and cultures. These semantic counterparts in the landscape are the result of long-term human-environment interactions, and the landscape has the capacity to become layered. Therefore, landscapes are palimpsestic environments. Understanding this multilayered structure of the landscape enables a better understanding of contemporary landscapes, ensuring that they are transferred into the future while preserving the natural and cultural codes behind them. In this context, the concept of "historic landscapes" emerged in England in the early 1990s, and it was understood that these landscapes contain traces of past societies' lives and their relationships with the environment. Therefore, uncovering these traces is essential. Following studies like LCA (Landscape Character Assessment), which have enabled the identification, archiving, and establishment of conservation-use strategies for contemporary landscape characteristics in England, the historical landscape characterization approach was developed. Parallel to the approach of the European Landscape Convention, the HLC (Historic Landscape Characterization) approach also advocates that each landscape is unique and distinct in its own right. In this sense, HLC is an essential tool for understanding the multilayered stratigraphy in landscapes and the counterparts of these layers preserved in contemporary landscapes. This approach, which attempts to understand historical character types in the landscape, is closely linked to LCA studies, which identify contemporary landscape characteristics, and both have the potential to feed into each other. Alaca Höyük is an archaeological settlement located in the Alaca district of Çorum Province, Turkey, which has been home to human settlement for approximately 6,000 years. Situated within the rural landscape of Central Anatolia, the mound is located 55 km south of Çorum, 14 km west of the town center of Alaca, and 35 km northeast of Hattusa, the capital of the Hittite Empire (Boğazköy). As with similar examples, the modern settlement of Alaca Höyük has been shifted to just outside the mound due to scientific archaeological excavations that began in 1935. The landscape creates a dynamic view, where the typical steppe landscape is interrupted by settlement areas, archaeological sites, agricultural landscape features, and natural landscape elements. The region has agricultural fields fed by Deregeçidi Stream, a tributary of Budaközü Stream. Budaközü Stream flows into the Delice River, one of the main branches of the Kızılırmak (ancient Halys). The valleys, rivers, and underground water sources surrounded by the Kızılırmak have been irrigated, making the area fertile. Alaca Höyük is located in one of these fertile valleys. In this context, the study area holds significant ecological history with both natural and human-shaped landscape elements. Historically, Alaca Höyük and its surroundings bear the traces of various cultural periods as a palimpsest landscape. The region encompasses four main cultural layers throughout history: the Chalcolithic Period (4000-3000 BCE), Early Bronze Age (3000-2000 BCE), Late Bronze Age/Hittite Empire (1500-1200 BCE), and Hellenistic, Roman, Byzantine, Seljuk, and Ottoman periods (300 BCE-AD 1923). These rich historical, cultural, economic, and ecological layers provide an important research area for understanding the co-evolution of human-environment relationships in the region. Studying the multilayered structure of this landscape allows for a broader understanding of changes and human interventions in the environment over time. This study provides an analytical perspective on the capacity of contemporary landscapes to encapsulate long-term human-environment interactions, focusing on the landscape of Alaca Höyük and its environs. The primary objective of the research is to uncover this embedded capacity within the landscape, reveal the shifts in meaning created by these traces, and transform the fragmented narratives generated by mixed-method approaches into a holistic narrative. The research questions addressed are: (1) What are the long-term changes in the landscape of Alaca Höyük and its surroundings, and how can these changes be interpreted in terms of human-environment relationships? (2) How can the study's outcomes be used to understand potential changes in the landscape? (3) How can the long-term human-culture-environment relationships in the landscape of Alaca Höyük and its surroundings be translated into a visual and textual narrative? The research objectives are to identify contemporary landscape characteristics, understand historical landscape features, analyze landscape change and fragility through land cover and land use, elucidate the shifts in meaning within the landscape driven by cultural factors, and represent these transformations through a diachronic narrative approach. The preservation and transmission of historically and culturally rich landscapes are crucial today, especially with the increasing human-centered landscape changes and their increasing vulnerability. To achieve this goal, it is necessary first to identify the characteristic features of these landscapes, uncover their historical traces, and analyze the directions of the physical and semantic changes. Such an approach moves beyond viewing landscapes merely as spatial formations, revealing their qualities as areas that have been perceived as "places" by different cultures, with meaning attached to them. By uncovering the shifts in meaning within landscapes, this approach facilitates the sharing of these "meanings," which are often overlooked, with both visitors and local communities. This method enhances the understanding of these areas from a physical perspective and strengthens their connection to societal values and increases their cultural significance. For the realization of these goals, the study employs a mixed-method approach, utilizing LCA (Landscape Character Assessment), HLC (Historic Landscape Characterization), and LULCc (Land Use/Land Cover Change). LCA was used to understand the current state, HLC to explain historical landscape characteristics, and LULCc to analyze changes based on land use and cover, particularly to highlight landscape fragility in the face of global crises such as climate change. In the LCA study, parametric methods were used to combine different thematic maps, after which landscape units were defined, and results were interpreted with the help of a field visit to identify contemporary landscape character areas. Similarly, HLC was integrated with different methods in the thesis, including remote sensing techniques, least-cost analysis, site basin analysis, retrogressive analysis, and systematic literature review. This integration aimed to increase the temporal depth behind landscape characters and create alternative approaches for sites like Alaca Höyük, where historical data is insufficient. In the LULCc method, CORINE data, landscape character areas derived from LCA outputs, and expert opinions were used to determine the vulnerabilities of these areas. The results derived from these mixed-method approaches have yielded significant insights, particularly for understanding historical and cultural landscapes like Alaca Höyük and its surroundings. As the research progressed toward its conclusion, these findings unveiled the grounded theory: Landscape undergoes semantic transformations driven by temporal leaps introduced by cultural agents. This transformation derives from the political nature of the landscape, which evolves in form alongside shifts in centralized authority. The research revealed the grounded theory: Landscape undergoes semantic transformations driven by temporal leaps introduced by cultural agents. It has been developed through a diachronic narrative informed by the results of mixed-method approaches, which integrate both qualitative and quantitative methodologies in alignment with a Braudelian perspective. It demonstrates that landscapes can be better understood through methodologies that synthesize diverse research approaches. Moreover, a participatory process is recommended for future studies, including local stakeholders, decision-makers, and experts. This engagement has the potential to enhance the semantic richness embedded within landscapes, ensuring their cultural and historical significance is better preserved and interpreted. In conclusion, this thesis highlights the dynamic and palimpsest nature of landscapes, showing their capacity to embody long-term socio-ecological, economic, and political transformations. By integrating diverse methodologies, the study not only advances the understanding of Alaca Höyük and its surrounding landscape but also provides a framework for interpreting historical landscapes as evolving entities enriched with both tangible and intangible values.
Tarihsel peyzajların anlamsal ve mekansal evriminin karma yöntem yaklaşımıyla ortaya konulması: Alaca höyük örneği
Thesis (Ph.D.) -- Istanbul Technical University, Graduate School, 2025
Keywords: Cultural landscape; Kültürel peyzaj; Landscape archeology; Peyzaj arkeolojisi